Pacific Northwest ferns and their allies - Taylor, Thomas Mayne Cunninghame, 1904-1983 (Heritage., 1970)
This is the first comprehensive treatment of the pteridophyte flora of the large area comprising Oregon, Washington, British Columbia, the Yukon Territory, and Alaska to the Arctic Ocean.